Lek Territory Size and the Evolution of Leks: A Model and a Test Using an Ungulate With a Flexible Mating System - Isvaran, Kavita (Frontiers in Ecology and Evolution, 2021)
Despite many decades of research, the evolution of the rare and unusual lek-mating system continues to be debated. The key question is: why do males defend tiny territories clustered together in an aggregation when the costs of doing so are so high? Theory and empirical work on lek evolution typically focus on why males cluster their territories. Surprisingly, the other characteristic feature of classical leks, which is the unusually small size of lek-territories, has received very little attention. Here, I argue that understanding the factors favouring the reduced size of lek-territories can provide fresh insights into the evolution of leks. I used the variable mating system of an Indian antelope, the blackbuck (Antilope cervicapra), to investigate lek territory size. Because there are few quantitative models of mating territory size, I first constructed a spatial simulation model of territory size based on male competition costs and on mating benefits generated by a female bias for mating on central lek-territories, the processes most likely to influence lek-territory size. The model generated much systematic variation in territory size within a territory-cluster and also across territory-clusters varying in the number of territorial males. I tested predictions from the model using comparative data on territory size from six blackbuck populations, and detailed spatial and temporal data from an intensively-studied population. Empirical analyses strongly supported model predictions and assumptions. Based on these findings, I present a novel hypothesis for the small size of classical lek-territories. I suggest that much of the variation in the size of lek-territories can be explained by the competition that arises from a female bias for mating on central territories and that is intensified by the number of territorial males in an aggregation. Thus, the reduced size of classical lek-territories is likely a consequence of a central mating advantage in large aggregations. I present a framework for the evolution of leks that explicitly incorporates the evolution of reduced territory size alongside the evolution of male clustering. This framework can also help explain other forms of mating systems that are based on the defense of mating territories by males.